Sinomenine in cerebral ischemia: mechanisms, delivery strategies, and the emerging multifunctional biomaterials of the bone–brain axis - Li, Xiang; Zhang, Xinyi; Wang, Tingyu; Li, Hangyu; Li, Yuxuan; Liu, Jianchun; Bai, Yuqi (Frontiers in Medicine, 2025)
Cerebral ischemia, a leading cause of neurological disability and death, is characterized by reduced cerebral blood flow that induces hypoxia, neuronal injury, and irreversible brain damage. Its complex pathophysiology involves neuroinflammation, oxidative stress, glial cell activation, disruption of the neurovascular unit, and increasingly recognized bone–brain axis crosstalk. Sinomenine (SIN), a bioactive alkaloid derived from Sinomenium acutum, exhibits notable anti-inflammatory, antioxidant, and immunomodulatory properties, and has shown protective effects on the cardiovascular and nervous systems. However, the clinical application of SIN is limited by its poor pharmacokinetic properties, such as low oral bioavailability and a short half-life. To address these limitations, nanotechnology-based delivery systems have been designed to enhance its stability, brain-targeting ability, and therapeutic potential. Recent studies also highlight the potential of leveraging the bone–brain axis as a novel route for SIN delivery, offering enhanced targeting of ischemic brain tissue. This review synthesizes current evidence on the neuroprotective mechanisms of SIN, with particular focus on its modulation of the bone–brain axis and the advances in delivery technologies. Collectively, these insights support the therapeutic potential of SIN-based nano-delivery platforms targeting the bone–brain axis in the treatment of cerebral ischemia.